STRATEGI KEPALA MADRASAH DALAM MENINGKATKAN JUMLAH SISWA DI MADRASAH TSANAWIYAH YAYASAN PENDIDIKAN SOSIAL DAN MA’ARIF 2 SIDOARJO - tri, Tri Wahyu Ningsih; M.Athoiful Fanan (ISLAMIC EDUCATION MANAGEMENT STUDY PROGRAM, 2023)
Strategic Head of Madrasah in Increasing the Number of Students in Madrasah Tsanawiyah Ma'arif 2 Sidoarjo Education and Social Foundation.Strata 1 program of Islamic Education Management Study Program STAI An Najah Indonesia Mandiri Sidoarjo. This study aims to know and describe the Strategy of the Head of Madrasah in Increasing the Number of Students in Madrasah Tsanawiyah Ma'arif 2 Sidoarjo Education and Social Foundation and the Challenges and Obstacles of Madrasah Heads in increasing the number of students in Madrasah Tsanawiyah Ma'arif 2 Sidoarjo Education and Social Foundation. The method used is the Quality research method, this research is a field research conducted directly in its place, namely at Madrasah Tsanawiyah Ma'arif 2 Sidoarjo Education and Social Foundation.The sources of research data used in this study are primary (main) data sources and secondary (supporting) data sources. Primary data were obtained through direct interviews with school leaders. Then secondary (supporting) data sources are obtained from the results of documentation, namely in the form of a brief history, organizational structure, research location and other documentation results related to the Madrasah Head Strategy. This study resulted in the strategy of the head of the madrasah and the obstacles and challenges in accepting students at Madrasah Tsanawiyah Ma'arif 2 Sidoarjo Education and Social Foundation through several strategies and programs, namely by building a network of partnerships to surrounding schools and target schools, providing good services, and promos throughout the year